The Implementation of the Latest Curriculum in Indonesia: Perspectives and Challenges - Werdiningsih, Dyah; Sunismi.,; Imron Azami, Mochamad (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this study consists of two main discussions namely how the perception of lecturers on optimizing the implementation of MBKM and how the perception of lecturers on the mechanism for granting the equivalent of MBKM in study program curriculum. The research design was carried out using data from SPADA DIKTI and 309 lecturers from University of Islam Malang as a respondent of this study and analyzed using SPSS 16 version. Descriptive quantitative was used as a research method to deeply describe about data. The result showed that lecturers have positive perception about the implementation of MBKM at University of Islam Malang regarding with the existence of similar program of MBKM, published MBKM curriculum and the involvement of lecturers in preparing the implementation of MBKM. Further, the majority lecturers already know the mechanism of how to equivalent the credits of MBKM program towards their study programs curriculum by choosing structured forms.